2002
DOI: 10.1029/2001jd001261
|View full text |Cite
|
Sign up to set email alerts
|

Role of temperature history in polar stratospheric cloud sightings

Abstract: [1] In this paper, aerosol data from the Polar Ozone and Aerosol Measurement (POAM) satellites between 1994 and 1998 are used to explore the existence of polar stratospheric clouds (PSCs) in the Antarctic winter stratosphere. Multiwavelength aerosol extinction data are combined to yield aerosol volume density which is compared with that generated from theoretical equilibrium models for nitric acid trihydrate (NAT) particles and supercooled ternary solution (STS) droplets at 30 mb. As winter progresses, PSC vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…In summary, although there are uncertainties of the UKMO temperature data, cold temperature histories are associated with the PSCs that we report in Figure 6. This is consistent with the suggestion of Steele et al [2002] based on their statistical analyses.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In summary, although there are uncertainties of the UKMO temperature data, cold temperature histories are associated with the PSCs that we report in Figure 6. This is consistent with the suggestion of Steele et al [2002] based on their statistical analyses.…”
Section: Discussionsupporting
confidence: 92%
“…To investigate this possibility, air mass trajectories on isentropic surfaces are calculated to investigate whether air masses experienced unusual temperature histories. Steele et al [2002] suggested from analyses of POAM aerosol data that factors other than temperature and temperature history are partially responsible for the formation of NAT PSCs although the occurrence probability at the NAT condensation temperature could be higher in air that has a previous cold temperature history.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the air masses were below T ICE for short periods before reaching McMurdo, where a warming occurred in most cases. The formation of PSCs in the warming phase has been reported to be more frequent also by POAM III Antarctic measurements [ Steele et al , 2002].…”
Section: Back‐trajectory Analysismentioning
confidence: 99%
“…Larsen et al (1997) presented evidence from Arctic balloonborne backscatter sonde observations for the effects of temperature history on NAT PSC formation, such as temperature oscillations and duration of exposure below T NAT . In a study of Antarctic POAM PSC observations, Steele et al (2002) concluded that other factors besides temperature history are likely to be a critical aspect of NAT PSC formation. The presence of aerosol impurities such as soot, meteoritic debris, and effects of ionization by cosmic rays have been proposed as agents which may act to promote freezing (Zondlo et al, 2000;Yu, 2004;Voigt et al, 2005).…”
Section: Nucleation Processesmentioning
confidence: 99%